Effect of Antiulcer on the Liver functions - A.L Aumr Thaar Joad; Omar Mohammad Hussein; Ihab Shihab Ahmed; Ali Abdulrahman Rejab; Omer Faiz Hassan; Wael Abdulrazak Abdullah (College of Pharmacy / Mustansiriyah University, 2018)
This study was done in Samarra city from 2-8-2015 until 22-12-2015 and 105 sample was collectedand divided to three groups. The first group 35 patientswere take Ranitidine as antiulcer drug and 35 patients were take Omeprazole antiulcer drug and 35 subjects as control. Patientscomparison were done between each group with control get a result if there is any effect on Liver function that the result were decrease in Alanine transferese (ALT), Aspartate transferese (AST), Alkaline phosphatase (ALP) and serum Total Protein (S. Total Protein), and we observed both of Ranitidine and Omeprazole not effect on total serum bilirubin (T.S.B) . The comparison between the two drugs in the impact on function convergent.